Factors associated with severe malnutrition among children under five-year old in Yogyakarta during the economic crisis - Endy P. Prawirohartono, Endy P. Prawirohartono (Universitas Gadjah Mada, 2002)
Background: Malnutrition is a problem in under five-year old children. During the economic crisis, the nutritional status of this group has decreased. There are variety of risk factors related to severe malnutrition. Some risk factors are preventable. Recognition of preventable risk factors is important in the management of severely malnourished children in the community.Objective: To determine factors associated with severe malnutrition among under five-year old children in Yogyakarta during the economic crisis.Methods: A case control study conducted in Sleman and Bantul Districts. Thirty four severely malnourished children and 68 controls of well nourished children were enrolled in this study. There were 6 group of variables consisted of 21 factors analyzed in this study. A logistic regression analysis was done to calculate OR and 95%Cl.Results: Univariate analysis showed that low educated mother, mother who works outside home, bad water disposal, non-breastfed children, and tuberculosis were associated with severe malnutrition where their OR and 95%Cl were 2.96 (1.26 - 6.94), 2.79 (1.15 - 6.77), 12.33 (3.44 - 44.24), 4.13 (1.70 -10.02) and 9.03 (2.29 - 35.62) respectively. Using multivariate analysis only non-breastfed children, tuberculosis and bad water disposal related to severe malnutrition with OR and 95%Cl 7.01 (1.35 -36.48), 11.52 (1.43 - 92.64) and 32.64 (5.44 - 195.90) respectively.Conclusions: Breastfeeding plays important role to support nutrients and other benefits to nutritional status of the children during the economic crisis. Tuberculosis is still a main factor related to severe malnutrition compared to acute diseases.Keywords: malnutrition - under five - risk factors - breastfeeding - tuberculosis